THE USE OF MODERN INFORMATION TECHNOLOGY IN PEDAGOGY - Kenjebayeva Gulnur Maratovna (Academia Science Repository, 2023)
Today in our country, equal attention is paid to all areas. In particular, the field of Education. That is why pedagogy is important as a programming area in the training of young professionals. In particular, the use of modern technologies in the education and education of young people, their introduction into education has become a priority. In this article, the author covers in detail the role of pedagogical technologies and modern technologies in pedagogy.